Estudo do processo de secagem em leito de espuma de cenoura, tomate, beterraba e morango - Roncheti, Elder Felipe Silva (2014)
In general, agriculture products are produced on a large scale and this productivity grows in proportion to its consumption. Therefore, another factor that also increases proportionally is the post-harvest losses, which suggests the use of technologies to increase the use of these products, mitigating waste and increasing its shelf life. Also, the product should be offered during off-season. In the present study, a drying technology in a foam beddryer was used toapply on carrots, beets, tomato and strawberry, which are products widely produced and consumed in Brazi l. In this study, the four products were submitted to a foam mat dryer with air circulation under controlled temperature of 40, 50, 60, 70 and 80 ºC. The description of drying kinetics was held according to mathematical models for each temperature of drying air. Furthermore, it was proposed a generalized mathematical model adjusted by nonlinear regression. The model by Page, obtained a better adjustment on the drying data in all of the products tested, with a coefficient of determination (R²) greater than 98% in all of the tested temperature. In addition, it was possible to model the influence of air temperature on the parameter k of the Page model by using an exponential model. The coefficient of effective diffusion increase with the growth of the temperature, presenting values between 10-8e 10-7 m².s-¹ for the process temperatures. The relationship between the coefficient of effective diffusion and the drying temperature may be described by Arrhenius equation.